#### Answer

slope = $\frac{3}{2}$
y-intercept: $(0, 1)$
Refer to the graph below.

#### Work Step by Step

Solve for $y$:
$y-\frac{3}{2}x-1=0
\\y-\frac{3}{2}x-1+1=0+1
\\y-\frac{3}{2}x=1
\\y-\frac{3}{2}x+\frac{3}{2}x=1+\frac{3}{2}x
\\y=\frac{3}{2}x+1$
This means that the given equation is equivalent to $y=\frac{3}{2}x+1$.
RECALL:
The slope-intercept form of a line's equation is $y=mx+b$ where $m$=slope and $(0, b)$ is the line's y-intercept.
Thus, the equation $y=\frac{3}{2}x+1$ has a slope of $\frac{3}{2}$ and a y-intercept of $(0, 1)$.
To graph the equation, perform the following steps:
(1) Plot the y-intercept $(0, 1)$.
(2) Use the slope to plot a second point.
Since the slope is $\frac{3}{2}$, from $(0, 1)$, move 3 units up (the rise) and 2 units to the right (the run) to reach the point $(2, 4)$. Plot $(2. 4)$.
(3) Connect the points using a straight line.
(Refer to the graph in the answer part above)